2007
DOI: 10.1080/19404476.2007.11462047
|View full text |Cite
|
Sign up to set email alerts
|

Methods and the Middle: Elementary and Secondary Preservice Teachers’ Views on Their Preparation for Teaching Middle School Social Studies

Abstract: The majority of middle school teachers are prepared in either generalist elementary programs or subjectspecific secondary programs, yet researchers and teacher educators have little understanding of the ways in which these divergent pathways prepare teachers for working at the middle school level. In this study, preservice teachers from an elementary and a secondary preparation program were interviewed about their conceptions of teaching social studies at the middle school level. The results indicated that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 8 publications
(6 reference statements)
0
12
1
1
Order By: Relevance
“…For example, given the predominance of females in the elementary group, it might be that females are more likely than males to hold high expectations for middle school students. Although a pilot study (Conklin, 2007) indicated the potential importance of gender as an influence on preservice teachers' beliefs about middle school students' capabilities, the data from the present study do not appear to support this explanation. For example, on the survey question that asked preservice teachers to select an appropriate middle school assessment (see Table 6), all of the secondary preservice teachers who selected the high-level cognitive assessment-on both the pre-and post-survey-are male.…”
Section: The Role Of Other Influencescontrasting
confidence: 99%
“…For example, given the predominance of females in the elementary group, it might be that females are more likely than males to hold high expectations for middle school students. Although a pilot study (Conklin, 2007) indicated the potential importance of gender as an influence on preservice teachers' beliefs about middle school students' capabilities, the data from the present study do not appear to support this explanation. For example, on the survey question that asked preservice teachers to select an appropriate middle school assessment (see Table 6), all of the secondary preservice teachers who selected the high-level cognitive assessment-on both the pre-and post-survey-are male.…”
Section: The Role Of Other Influencescontrasting
confidence: 99%
“…In their review of the research on teacher education and development in the social studies, Crocco and Linvingston (2017) referenced Shulman's (1986) pedagogical content knowledge (PCK)-a confluence of instructional know-how and disciplinary background-as a reference point for quality teaching. Yet, as noted by Conklin (2007Conklin ( , 2008Conklin ( , 2010), PCK and the path toward middle grades social studies teaching can take numerous turns that may influence teachers' views of younger adolescents' cognitive capabilities as well as instructional decision-making.…”
Section: Emphasis On Quality Teachingmentioning
confidence: 99%
“…Other studies have sought to understand teachers’ attitudes toward a particular facet of the middle level concept (Dellinger, 1992; Evola, 2004; Fisher, 2012; Korejwa, 2009; Morgan-Conner, 1995; Updegraff, 2011). In the most recent line of inquiry, researchers have documented the impact of teacher knowledge (gained primarily in preservice) of This We Believe on the classroom environments created by these educators upon graduation (Conklin, 2007; Huss 2000, 2004; White, Dever, Ross, Jones, & Miller, 2013). These studies suggest that the success of middle level education is intimately tied to the beliefs of and principles used by practicing middle level teachers when designing and implementing curriculum.…”
mentioning
confidence: 99%